Enhancing Emergency Medical Services with Smart Glasses Technology for Optimal Ambulance Positioning in Simulated Critical Patient Care Scenarios - Apiratwarakul K; Khemtong S; Cheung LW; Pearkao C; Ienghong K (Journal of Multidisciplinary Healthcare)
Korakot Apiratwarakul,1 Sukanya Khemtong,1 Lap Woon Cheung,2,3 Chatkhane Pearkao,4 Kamonwon Ienghong1 1Department of Emergency Medicine, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand; 2Accident & Emergency Department, Princess Margaret Hospital, Kowloon, Hong Kong; 3Department of Emergency Medicine, Li Ka Shing Faculty of Medicine, The University of Hong Kong, Pokfulam, Hong Kong; 4Department of Adult Nursing, Faculty of Nursing, Khon Kaen University, Khon Kaen, ThailandCorrespondence: Kamonwon Ienghong, Department of Emergency Medicine, Faculty of Medicine, Khon Kaen University, 123 Mittraphap Road, Mueang Khon Kaen District, Khon Kaen, 40002, Thailand, Tel +66 43 366 869, Fax +66 43 366 870, Email Kamonwan@kku.ac.thPurpose: To implement smart glasses with augmented reality distance measuring technologies in conventional self-assessment techniques, to improve ambulance location accuracy during simulated emergency scenarios.Patients and Methods: Eighty-two emergency medical services professionals participated in this simulation-based study at Srinagarind Hospital, Thailand. Participants positioned ambulances in simulated chemical, biological, radiological, nuclear, and explosives (CBRNE) and non-CBRNE scenarios using traditional self-assessment methods, followed by positioning using smart glasses technology after a 120-minute training session. Smart glasses equipped with a measurement-augmented reality application were utilized. Positioning accuracy was assessed.Results: The participants had a median age of 36.1 years, with males comprising the majority (63.4%). Emergency nurse practitioners and students constituted the largest group (56.1%). Most participants (51.1%) reported over a decade of EMS experience. Smart glasses technology significantly improved positioning accuracy in both scenario types (p< 0.001). In CBRNE scenarios, accuracy increased from 47.6% with self-assessment to 83.3% with smart glasses. In non-CBRNE scenarios, accuracy improved from 66.7% to 83.8%.Conclusion: Smart glasses technology with augmented reality distance measurement capabilities substantially enhances ambulance positioning accuracy, particularly in complex CBRNE scenarios. The technology’s ability to standardize performance across emergency types, and potentially across responder experience levels, suggests significant value for improving emergency medical service delivery, patient care, and responder safety.Keywords: augmented reality, decision making, emergency mobile units, technology